PROGRAM PENINGKATAN KEBERHASILAN SATUAN PENDIDIKAN AMAN BENCANA (SPAB) DALAM MENGHADAPI ANCAMAN BENCANA MULTI-HAZARD PADA SANTRI DI PONDOK PESANTREN NURUL HAKIM KABUPATEN LOMBOK UTARA NUSA TENGGARA BARAT - Setya Haksama; M. Farid Dimjati Lusno; Chairun Nasirin; Rahmani Ramli; Endy Bebasari Ardhana Putri; Ni Nyoman Santi Tri Ulandari; Arista Kusuma Wardani; Febriati Astuti; Diansanto Prayoga; Aisyah Maldha Aprezona; Abdillah Maulana Satrioaji; Syahprevi Rayyan Zeinsar Prawirosoedirdjo (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
North Lombok Regency is an area highly prone to multi-hazard disasters such as earthquakes, floods, landslides, and tsunamis. This condition requires strong preparedness, including within Islamic boarding schools (pesantren) as educational and residential institutions. Nurul Hakim Islamic Boarding School faces several challenges, including low awareness and understanding of disaster risks, limited resources, and the absence of systematic disaster education in its learning activities. This community service program was conducted at Nurul Hakim Islamic Boarding School, North Lombok, aiming to enhance students’ knowledge, skills, and awareness of disaster preparedness through the implementation of the Safe School Program (Satuan Pendidikan Aman Bencana—SPAB). The program was carried out in four stages: preparation and socialization, training and practice, mentoring and evaluation, and advocacy for sustainability. The results showed an improvement in participants’ average scores from 6.14 (pre-test) to 6.88 (post-test), indicating better understanding of disaster preparedness. Participants also demonstrated practical skills in mapping evacuation routes and understanding emergency response procedures. The advocacy activities fostered cross-sector commitment to integrating SPAB into the school’s routine programs. These findings imply that an educational and participatory approach effectively strengthens pesantren capacities in disaster preparedness. In conclusion, SPAB implementation contributes to building disaster-resilient Islamic boarding schools through collective awareness and institutional collaboration